COMPARATIVE ANALYSIS OF DETERMINING PROFIT MARGINS FOR CANDLENUT PRODUCT SALES BETWEEN DOMESTIC AND EXPORT MARKETS FOR UMKM IN CENTRAL LOMBOK REGENCY - Lalu Adiyatma Taopikul Hadi; Alfisahrin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study compares product profit margins between the domestic and export markets of UMKM in Central Lombok. The analysis shows an average domestic margin of 5% (n=10, standard deviation 3%), while the export margin is significantly higher at 32% (n=1, standard deviation 5%). A t-test demonstrated a significant difference in margins (p-value <0.05). The export process requires more raw materials, but the profit potential is much greater. These findings can serve as a reference for UMKM in determining optimal candlenut marketing strategies. This is a comparative descriptive study using a quantitative approach. The study was conducted in Central Lombok Regency, West Nusa Tenggara Province. Data were obtained through structured interviews with UMKM to obtain information on production processes, pricing, marketing strategies, and profit margin calculations. A questionnaire was used to obtain data on production costs, selling prices, sales volumes, and profit margins.